Diagnostic value of the gradient-echo in-phase and out-of-phase MRI sequence in the characterization of benign and malignant hepatic focal lesions - Hoda A Kareem; Yasser A Aal (Wolters Kluwer Medknow Publications, 2020)
Background MRI is an excellent imaging modality to evaluate the liver which is vulnerable to a spectrum of neoplastic and nonneoplastic conditions. Out-of-phase T1 weighted (T1W) gradient-echo imaging is a highly accurate technique to distinguish focal hepatic steatosis from neoplastic masses. Aim This study aimed to demonstrate the diagnostic value of gradient-echo in-phase and out-of-phase MRI sequence in the characterization of benign and malignant hepatic focal lesions. Patients and methods This study is carried out on 89 patients with 100 hepatic focal lesions; their ages ranged from 32 to 76 years (mean, ±52 years), who traveled for MRI liver for the diagnosis and characterization of hepatic focal lesions. MR examination was performed including T1WI, T2WI, postcontrast dynamic enhanced T1WI followed by gradient-echo in-/out-of-phase MRI sequences. Results The 100 hepatic focal lesions proved to be: 17 focal fatty infiltration, one lipoma and eight fatty-spared area (FSA), 11 hemangioma, 10 regenerative cirrhotic nodules (RN), eight siderotic liver nodules, 12 dysplastic liver nodules, 23 hepatocellular carcinomas, seven metastatic, and three lymphoma. At conventional MRI, most of the benign hepatic focal lesions exhibit iso/hyperintense signals at T1WI and iso/hypointensity at T2WI. However, nearly all malignant lesions exhibit mainly hypointense signals at T1WI and mild hyperintensity at T2WI. At DCE T1WI: focal fatty infiltration and FSA, RN, and siderotic liver nodules take no enhancement; hemangiomas showed marginal arterial enhancement with gradual filling and there is arterial contrast enhancement with venous washout in hepatocellular carcinomas and arterial enhancement with or without washout in metastatic lesions; however, lymphomatous lesions showed temporary perilesional arterial enhancement with delayed contrast enhancement. The gradient in-/out-of-phase sequence: accurately diagnoses the all fat-containing lesions that showed moderate hyperintensity in the in-phase images and signal loss in out-of-phase images, while FSA exhibit in-phase isointensity and hyperintensity in out-of-phase images while all other benign and malignant hepatic focal lesions revealed hypointense signals in both in-/out-of-phase images. Conclusion Gradient-echo in-/out-of-phase sequence is a simple and noninvasive method that can aid in the diagnosis and characterization of benign and malignant hepatic focal lesions with 100% accuracy in the diagnosis of fat-containing lesions. Also, it can differentiate RN from dysplastic liver nodules that is considered as premalignant lesions and improve the malignant hepatic focal lesion definition.